MENINGKATKAN KINERJA GURU DALAM MELAKSANAKAN KEGIATAN EKSPLORASI, ELABORASI DAN KONFIRMASI PADA PEMBELAJARAN IPA - Herwandi, Herwandi (Jurnal Vidya Karya, 2012)
This study aims to improve teacher performance in conducting exploration, elaboration, and confirmation in science classroom. The School Action Research conducted in fourth and fifith grade of SDN Sidorejo Tanjung consists of 2 (two) cycles. Research subjects are two science teachers in fourth and fifth grade. The findings revealed that through establishing action in 2 cycles, fourth grade science teachers ability to conduct exploration improves from 8,0 to 12,0; elaboration improves from 9,0 to 13,0, and confirmation improves from 8,0 to 12,5. For fifth grade science teacher, teachers ability to conduct exploration improves from 6,5 to 12,0; elaboration improves from 6,0 to 12,0; and confirmation improves from 7,3 to 12,0. In general, teachers’ ability to conduct exploration, elaboration, and confirmation increase from 52,25% in cycle 1 (good category) to 78% in cycle 2 (excellent).